2021
DOI: 10.3390/vaccines9030224
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of a Novel Intranasal Influenza Vaccine (NasoVAX): A Phase 2 Randomized, Controlled Trial

Abstract: Annual influenza vaccination greatly reduces morbidity and mortality, but effectiveness remains sub-optimal. Weaknesses of current vaccines include low effectiveness against mismatched strains, lack of mucosal and other effective tissue-resident immune responses, weak cellular immune responses, and insufficiently durable immune responses. The safety and immunogenicity of NasoVAX, a monovalent intranasal influenza vaccine based on a replication-deficient adenovirus type 5 platform, were evaluated in a placebo-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…In addition to lower safety requirements than assays using replication-competent SARS-CoV-2, pseudotyped virus assays are well positioned for HTS testing of antibody responses elicited by natural infection, vaccination, and now, critically, to new viral variants of concern (VOC), as reported for other viruses ( 60 62 ). One limitation of the current study was that only two strains, Wuhan and D614G, were tested.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to lower safety requirements than assays using replication-competent SARS-CoV-2, pseudotyped virus assays are well positioned for HTS testing of antibody responses elicited by natural infection, vaccination, and now, critically, to new viral variants of concern (VOC), as reported for other viruses ( 60 62 ). One limitation of the current study was that only two strains, Wuhan and D614G, were tested.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, nasal administration of replication-deficient human Ad5-vectored vaccines, such as AdCOVID, mimic natural infection of respiratory viruses and stimulate strong protective immunity, both systemically and mucosally, while maintaining an established clinical safety profile [ 47 , 48 , 49 , 50 , 51 ]. Intranasal vaccination stimulates mucosal IgA antibodies, providing a first line of defense at the point of respiratory pathogen inoculation [ 52 ], which correlates well with protection from respiratory infections such as influenza [ 53 , 54 , 55 ]. Numerous studies have demonstrated the ability of intranasally administered vaccines to block transmission of influenza between infected and naïve cage-mates [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In face of the encouraging results from the mixed vaccine regimens using RNA vaccine first followed by adenoviral vector vaccines [59][60][61][62] , it might be worthy to utilize an intranasal application for the viral vector boost immunization. This atraumatic, non-invasive application might also reduce the systemic side effects reported for the viral vector vaccines 79,80 .…”
Section: Discussionmentioning
confidence: 99%